Capital in the Corona crisis - Leo Kaas (Leibniz Institute for Financial Research SAFE, 2020)
The shutdown of entire industries during the corona crisis represents a completely new and huge challenge for economic policy. Particular attention is being paid to limiting the loss of income for people affected by unemployment and to ensuring the existence of businesses affected by closures and demand shortfalls. So far, the Federal Government of Germany has responded to these challenges with rapid and comprehensive measures. In particular, the aid programs for companies, which consist of tax reliefs and government-backed emergency loans, are designed to mitigate liquidity shortfalls and to prevent insolvencies. These programs are supplemented by direct transfers to smaller companies and self-employed workers. In the current situation, these unconventional measures are appropriate and urgently needed. As in "normal" recessions, companies are free to adjust their labor and capital inputs. However, such adjustments are costly: If, for example, workers are laid off, new workers will have to be recruited and trained after the end of the crisis. Such costs can be avoided, or at least reduced, by cutting working hours or resorting to temporary layoffs, and this is precisely why the provisions of short-time work schemes are currently being loosened in Germany.
Keywords: 330; Corona Crisis; Capital liquidations; Emergency loans